Memberikan Motivasi Kepada Pasangan Yang Mengalami Stroke Disabilitas Fungsional di Rumah - Esti, Amira; Johan, Trimonarita (Universitas Fort De Kock Bukittinggi, 2019)
Stroke is brain function disorder which can suddenly occur at any time. It can also cause physical defect such as stroke in moving organs, speech disorder, thinking process as the result of brain function disorder. Physical defect caused by stroke does not only affect the patient but also his or her spouse. The patient will be emotionally and physically dependent on his or her spouse. The objective of this research was to explore deeply the meaning of support from a spouse in taking care of a stroke patient who underwent functional disability. The research used descriptive phenomenological study. The data were gathered by conducting in- depth interviews and field-note. There were 12 respondents, taken by using purposive sampling technique give motivation to the participants who have stroke of functional disabilities at home. It is recommended that nurses, as educators for stroke patients apply their knowledge in doing their nursing care by involving the patients’ spouses and train them in taking care of stroke patients before discharging from hospitals. The respondents as the patients’ spouses should motivate and continuously lake the patients to the hospitals in order to see the patients’ development and to expedite the process of recovery. Keywords: Motivation, Couple, Disability Stroke